APPLICATION THE ACADEMIC OF SUPERVISION USING ARTISTIC AND COOPERATIVE DEVELOPMENT MODEL TO IMPROVE THE COMPETENCY OF PEDAGOGICAL FOR TEACHER IN ELEMENTARY SCHOOL PUTAT GEDE 1/94 SURABAYA - Soedjono Soedjono (LPPM STAI Muhammadiyah Probolinggo, 2021)
The development of teacher pedagogical competence in schools is a must, considering the teacher as the spearhead in learning. While the principal as a leader who has a function as a manager and supervisor has a strategic role in utilizing the teachers in the school. This research produces the following: 1. Principal supervision strategies to improve teacher pedagogical competence through the effective application of academic supervision with (a) conceptual skills; (b) interpersonal; and (c) technical. 2. Principal supervision approach to improve teacher pedagogical competence. The approach used (a) Directif Approach; (b) Non-directive Approach; and (c) Collaborative Approach. In this case, the core pedagogic competencies covered include: First, Mastering learning theory and principles of learning that educate with Second, Developing a curriculum related to the subjects being taught. Third, Utilizing information and communication technology in learning. (3) Implications for schools namely the creation of a conducive school atmosphere. the creation of effective learning by applying interesting learning methods, the implementation of curricula that are following the standards, and the implementation of ICT-based learning processes